Shining a Light on Dissipative Supramolecular Assemblies - Nieland, Esther; Voss, Jona; Schmidt, Bernd M. (Synlett, 2023)
We recently reported photoresponsive, dissipative, and dynamic covalent macrocycles that use visible-light photoswitching. Several other exciting contributions involving the use of metal–organic and metal-free supramolecular assemblies have been published back-to-back; here, we have a closer look at these contributions, together with an in-depth insight into our macrocyclic system.1 Introduction2 Photoswitchable Dissipative Supramolecular Systems3 Photoresponsive Dynamic Covalent Imine Macrocycles4 Conclusion
Keywords: photoswitchable assemblies; dynamic covalent chemistry; photochemistry; self-assembly; supramolecular chemistry; azobenzenes